Evaluation of Implementation Effect of Cervical Cancer Comprehensive Treatment Patients With Whole-Course High-Quality Care Combined With Network Continuation Care - Chen, Jing; Bai, Hui (Frontiers in Surgery, 2022)
Purpose: Discuss the implementation effect of cervical cancer comprehensive treatment patients applying whole-course high-quality care combined with network continuation care. Methods: From August 2020 to August 2021, 120 patients who met the inclusion criteria for comprehensive treatment of cervical cancer were divided into the regular group (n=60) who received conventional care and the joint group (n=60) who received whole-course high-quality care combined with network continuation care, according to the method of care. The comprehensive treatment cognition level, comprehensive treatment compliance, adverse reaction rate, quality of life questionnaire (QLQ-C30) score, self-rating anxiety/depression scale (SAS/SDS) score, and nursing satisfaction were compared between the two groups. Results: After care, the comprehensive treatment cognition score and comprehensive treatment compliance score were higher in the joint group than in the regular group (P < 0.05). After care, the incidence of radiation cystitis and radiation proctitis was lower in the joint group than that in the regular group (P < 0.05). After care, QLQ-C30 scores on symptom domains, functional domains, and single questions were higher in both groups than before care, and were higher in the joint group than in the regular group (P < 0.05). After care, SAS and SDS scores were lower in both groups than before care, and were lower in the joint group than in the regular group (P < 0.05). After care, the joint group was more satisfied with care than the regular group (P < 0.05). Conclusion: The implementation of cervical cancer comprehensive treatment patients with whole-course high-quality care combined with network continuation care has an ideal implementation effect, which can significantly increase the patient’s cognition and compliance with treatment, the incidence of adverse reactions is less, the quality of life and emotional state have also improved significantly, and care satisfaction has also increased accordingly.